해방기 오장환의 인민주권의 상상과 월북의 내적 논리 - 정영진(Jeong, Young-Jin) (한국시학연구, 2018)
식민지 시기 일체의 정치적 행위와 자유가 막혀서 절망적 감정에 빠져 있던 오장환에게 해방은 진취적인 행위가 가능한 시대를 여는 사건이었다. 그는 인민주권의 새 나라, 즉 인민민주주의 실현을 열망하면서 실천적 삶을 살아가고자 했다. 오장환이 상상한 인민주권의 새 나라는 평등한 권리를 보장받은 인민들이 즐겁게 노동하고, 자유롭게 문화생활을 향유할 수 있는 국가였다. 오장환은 인민주권이 확립된 독립국가 건설을 위해 투쟁의 현장으로 나아갔지만, 그곳에서 동지들처럼 실천으로 나아가지 못하는 자신의 소시민적 한계를 발견했다. 이에 대한 끈질긴 탐구가 해방기 시에 고스란히 나타났다. 오장환은 그의 시에서 이념형 인간은 실천 행위 속에서 완성되는 것임을 보여주었다. 이념은 실천 속에서 육체를 얻어야하며 그럴 때 형식주의에 떨어지지 않을 수 있다는 사실을 투쟁하는 인민들을 통해 오장환은 깨우쳤기 때문이다. 인민들 사이의 심연을 자기반성과 실천의 문제와 관련지어 사유했던 오장환은 그 심연을 자신의 실천의 동력으로 삼았다. 생활과 신체/감각이 다르고 그렇기에 실천의 양상도 다를 수밖에 없는 동지들과 함께 하면서, 마침내 집단 이성과 강력한 규율이 마련된 데서 행위/실천의 토대를 발견하였다. 집단 이성과 강력한 규율이 상대적으로 확립된 북한 체제에서 인민주권의 실질적 획득을 전망한 오장환은 월북을 선택했다고 할 수 있다. 해방기 오장환은 당대 이념적·담론적 차원에서 매끄럽게 구성된 인민주권과 인민민주주의를 상상하기보다는, 인민들 사이에 내재하는 심연을 매개로 상상했다. 그는 단일한 인민을 상상하지 않았다. 그의 시가 보여준 이 심연은 인민주권에 대한 다양한 사유를 촉발하고 인민에 대한 위계적 시선을 교란시키는 지점이다. 오장환이 한국 시와 민주주의를 사유할 때 유의미하게 고려되어야 하는 까닭이 여기에 있다. 또한 인민이 가르치고 지식인은 배우는 관계를 오장환의 시만큼 환하게 보여주는 경우는 드물다. 다시 말하면, 오장환 시에서 일반적인 계몽의 주체와 대상은 역전된다. 한국문학사에서 인민과 지식인의 관계 설정 문제가 복잡하고 까다로운 것이었다는 점을 떠올린다면, 해방기 오장환의 시의 독특함을 여기서도 발견할 수 있겠다. The national liberation opened an era for progressive activities for Oh Jang-hwan who had been in despair due to the prohibition of all political activities and depression of freedom during the Japanese colonial rule. He aspired for the realization of a new country with popular sovereignty, that is, people’s democracy, and wanted to live a practicing life. The new country with popular sovereignty imagined by Oh Jang-hwan was a nation in which the people guaranteed for equal rights could work merrily and enjoy cultural lives freely. Oh Jang-hwan proceeded to the field of struggle for the construction of an independent country by the establishment of popular sovereignty, but there he found his bourgeois limitation not practicing like his comrades. His persistent quest about it appeared clearly in his poems written in the liberation period. In his poems, Oh Jang-hwan showed that an ideological man is completed by practicing activities. Oh Jang-hwan realized through the struggling people that Ideology should be shaped by practicing and in doing so we do not fall down to formalism. Oh Jang-hwan thought the abyss among people in relation to his self-reflection and the problem of practicing and used the abyss as the momentum for his practicing. Working together with his comrades who had different life, body and sense and as a result a different pattern of practicing, he found the foundation for practicing and activity in the collective intelligence and a strong discipline. Anticipating a substantial realization of popular sovereignty in North Korea where collective intelligence and a strong discipline are established relatively better, Oh Jang-hwan chose to defect to North Korea. During the liberation period, Oh Jang-hwan did not imagine popular sovereignty and people’s democracy constructed smoothly in the dimension of the ideology and discourse of the times. Rather, he imagined with the media of abyss inherent among people. He didn’t imagine a single people. The abyss shown by his poems is the point that prompts various thoughts about popular sovereignty and disturbs the hierarchical view of people. That is why Oh Jang-hwan should be considered meaningful when we think of Korean poetry and democracy. Also, the poems of Oh Jang-hwan clearly show the relationship between the teaching people and the learning intellectuals. In other words, the ordinary relationship between the agent and the object in enlightenment is reversed in the poems of Oh Jang-hwan. Thinking the complex and difficult matter of setting the relationship between the people and the intellectuals in the history of Korean literature, we can find the unique character of the poems of Oh Jang-hwan during the liberation period here, too. KCI Citation Count: 6